The Management of Kyai Development Through Polite Languages to Form Akhlakul Karimah Santri in The Pesantren - Arum Maslachah; Sofyan Sauri; Helmawati Helmawati (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This study aims to describe how the management of kyai coaching through politeness in improving the morals of the santri at Miftahul Khoir Islamic Boarding School, Bandung City. This research uses a qualitative approach. While the method used is a case study (Case study) which is a process of collecting data and information in-depth, detail, intensive, holistic, and systematic about people, events, social backgrounds, or groups using various methods and techniques as well as many sources of information. to understand effectively how people, events, natural settings (social settings) operate or function in accordance with the context. The results showed that the management of kyai guidance through politeness in improving the morals of the santri was carried out through exemplary methods, training and habituation methods, and learning methods. Where through these methods the students are accustomed to saying greetings, speaking polite, politely, gentle, low self-esteem, and not speaking harshly.